"Everything Has Changed, and Nothing Has Changed in Journalism": Revisiting Journalistic Sourcing Practices and Verification Techniques during the 2011 Egyptian Revolution and Beyond. Issue 7 (9th August 2022) - Schapals, Aljosha Karim; Harb, Zahera
Abstract: Using the Egyptian Revolution as a case study, this article studies journalistic sourcing and verification through in-depth interviews with journalists in the United Kingdom. While the coverage of the event in the British media was dominated by civic, unofficial sources, interviews conducted in 2014 revealed that journalists only included these if no other sources were available. In fact, journalists voiced concern with regards to verification of online sources, and rarely included these as direct, first-hand accounts. Follow-up interviews conducted in 2020 point to developments journalism practice has undergone since, particularly in relation to open-source content verification. Overall, the picture we paint of British journalists' handling of content sourced from social media is one wedged between expressed enthusiasm and cautious scepticism.